2018
DOI: 10.1111/dom.13348
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypoglycaemia and risk of cardiac arrhythmia in patients with diabetes mellitus: A systematic review and meta‐analysis

Abstract: Our findings suggest that hypoglycaemia results in ECG alterations that are associated with increased risk of cardiac arrhythmia, which is associated with increased cardiovascular events and mortality. More clinical studies are needed to determine the cardiac risks of hypoglycaemia in individuals with diabetes, especially in Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 52 publications
(125 reference statements)
2
26
0
2
Order By: Relevance
“…Thus, it is worthwhile knowing, that especially during hypoglycaemia, CGM‐derived data need to be questioned and may require confirmation by capillary BG measurements. This is also true for proCGM when used as a diagnostic tool, both in routine care and in outcome studies where the duration and frequency of hypoglycaemia need to be interpreted with caution …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is worthwhile knowing, that especially during hypoglycaemia, CGM‐derived data need to be questioned and may require confirmation by capillary BG measurements. This is also true for proCGM when used as a diagnostic tool, both in routine care and in outcome studies where the duration and frequency of hypoglycaemia need to be interpreted with caution …”
Section: Discussionmentioning
confidence: 99%
“…This is also true for proCGM when used as a diagnostic tool, both in routine care and in outcome studies where the duration and frequency of hypoglycaemia need to be interpreted with caution. 2,18 Some limitations of previous studies (short duration of experiment, lack of home phase, lack of sleep phase) were addressed. However, our study is limited by the rather small number of participants and the potential pressure artefacts (ie, on which side was the patient sleeping with regard to sensor performance).…”
Section: Discussionmentioning
confidence: 99%
“…20 A recently published meta-analysis confirmed that hypoglycaemia can result in ECG changes associated with cardiac arrhythmias that are markers of increased risk of mortality and cardiovascular events. 21 Cardiac arrhythmias may be an underlying factor that explains our findings of increased risk of myocardial infarction, stroke, falls and fractures, and death following hypoglycaemia. Nevertheless, the effects of hypoglycaemia on the cardiovascular physiology of frail, multi-morbid older patients with diabetes remains unclear.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the study of Pistrosch et al of continuous glucose monitoring (CGM) and ambulatory cardiac monitoring found a link between hypoglycaemia and the occurrence of ventricular arrhythmias . A recently published meta‐analysis confirmed that hypoglycaemia can result in ECG changes associated with cardiac arrhythmias that are markers of increased risk of mortality and cardiovascular events . Cardiac arrhythmias may be an underlying factor that explains our findings of increased risk of myocardial infarction, stroke, falls and fractures, and death following hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia is classified into three levels based on the standard for hypoglycemia suggested by the recent American Diabetes Association (ADA) guideline [13], i.e., hypoglycemia alert value (mild hypoglycemia), clinically significant hypoglycemia (moderate hypoglycemia), and severe hypoglycemia. Severe hypoglycemia and clinically significant hypoglycemia are associated with an increased risk of macrovascular events, microvascular disease, and all-cause death [14][15][16][17][18]. Mild hypoglycemia is traditionally thought to be harmful and should be avoided if possible.…”
Section: Introductionmentioning
confidence: 99%